Technology enhanced learning: quality of teaching and educational reform 1st International Conference, TECH-EDUCATION 2010, Athens, Greece, May 19-21, 2010, proceedings - TECH-EDUCATION 2010 (Communications in Computer and Information Science, 2010)
It is a great pleasure to share with you the Springer CCIS proceedings of the First International Conference on Reforming Education, Quality of Teaching and Technology-Enhanced Learning: Learning Technologies, Quality of Education, Educational Systems, Evaluation, Pedagogies – TECH-EDUCATION 2010, Which was a part of the World Summit on the Knowledge Society Conference Series. TECH-EDUCATION 2010 was a bold effort aiming to foster a debate on the global need in our times to invest in education. The topics of the conference dealt with six general pillars: Track 1. Quality of Education – A new Vision Track 2. Technology-Enhanced Learning – Learning Technologies – Personalization-E-learning Track 3. Educational Strategies Track 4. Collaborative/ Constructive/ Pedagogical/ Didactical Approaches Track 5. Formal/ Informal/ and Life–Long Learning Perspectives Track 6. Contribution of Education to Sustainable Development Within this general context the Program Committee of the conference invited contributions that fall in to the following list of topics. Track 1: Quality of the Education – A new Vision • Teaching Methodologies and Case Studies • Reforms in Degrees • The European Educational Space • Academic Curricula Designs • Quality of Teaching and Learning • Quality and Academic Assessment • The School / University of the Future • Challenges for Higher Education in the 21st Century • New Managerial Models for Education • Financing the New Model for Education of the 21st Century • The Quality Milestones for Education of the 21st Century • Evaluation in Academia • The Role of Teachers • International Collaborations for Joint Programs/Degrees • Industry–Academia Synergies • Research Laboratories Management. Moodle 2.0: shifting from a learning toolkit to a open learning platform - Technology enhanced learning for people with intellectual disabilities and cerebral paralysis: the MAS platform - Student blogging: implications for learning in a virtual text-based environment - Confidence-based learning in investment analysis - Language teaching across the digital divide - EduSynergy: a simulation-based change management experience for higher education institutions - The study of educative network organizations in the city of Barcelona, Spain: the Nou Barris district - Experimenting design and implementation of an educational services management system based on ISO/IEC 20000 standard - Having your own automatic judge: EEWS - Mii school: new 3D technologies applied in education to detect drug abuses and bullying in adolescents - KP-Lab system: a collaborative environment for design, realization and examination of different knowledge practices - Machine learning support for human articulation of concepts from examples – A learning framework - Oratoria online: the use of technology enhaced learning to improve students’ oral skills - Legibility for users with visual disabilities - Assessment of andragogical attributes of distance learners - Moodle 2.0 web services layer and its new application contexts - Didactic scenarios and ICT: a good practice guide - Interactive whiteboard integration in classrooms: active teachers understanding about their training process - Teaching business simulation games: comparing achievements frontal teaching vs. eLearning - The VOLARE methodology: using technology to help changing the traditional lecture model - Towards an automatic forum summarization to support tutoring - Efficiency assessment of a blended-learning educational methodology in engineering - TELL(Technology-Enhanced Language Learning) and less-commonly taught languages: the case of modern greek A case study of modular-based project oriented learn in electrical engineering - Origami in education enhanced by computer technology: a Case Study of Teaching Hexaflexagon in Math class - Challenges of implementing ESD in the education sector; Experiences in Norway - Using automated assessment feedback to enhance the quality of student learning in universities: a case study - Lessons learned from deploying a video-based web 2.0 platform in an executive education context - Improving the scholarship of teaching and learning through classroom research - Which are the determinants of online students’ efficiency in Higher Education? - On the utility of ICT in the european higher education area: the bologna process and its implications in the innovation of the teaching and learning process - Computer programming: fail fast to learn sooner - Experiential collaborative learning and preferential thinking - Computer sciences applied to management at Open University of Catalonia: development of competences of teamworks - From workshop to the web: reflections on the journey in producing Vidcasts to enhance student learning - ‘Virtual learning-by-doing’ Teamwork KSA: strategic management simulation as an effective tool - The digital board in a university setting: Two real cases in Europe and East Africa - E-learning across cultural boundaries: a european perspective on technology acceptance - Using collaboration strategies to support the monitoring of online collaborative learning activity - Knowledge construction with social web tools - Information security threats analysis for e-learning - Employability: challenges for education and training systems - System and user characteristics in the adoption and use of e-learning management systems: a cross-age study - A comparative study on the influence between interaction and performance in postgraduate in-class and distance learning courses based on the analysis of LMS logs Education for sustainable development through the use of the second life : the use of a virtual museum for sharks - Quality of project management education and training programmes - ICT in the education of students with SEN: perceptions of Stakeholders - A haptic-based framework for chemistry education: experiencing molecular interactions with touch - The academic advising system in a virtual university - Course evaluation study in Europe: the current picture - Enhanced learning methodologies and the implementation of an identification course - The reforming of vocational teacher training colleges in Turkey - Multicultural Interdisciplinary Handbook (MIH): tools for learning history and geography in a multicultural and ICT perspective - A process for improving course quality based on Mid-semester feedback - The challenges of digital literacy in the context of the Spanish Government Educational Policies: the statement of the question - The role that web 2.0 currently Has and could have in the future in supporting the teaching of ICT design for all - Measuring technological and content knowledge of undergraduate primary teachers in mathematics - The workbook service in a learning virtual communities’ platform - Representations of disability: school and its cultural effects - Adaptative peer to peer data sharing for technology enhanced learning - E-learning as an opportunity for the public administration - Embedding educational design pattern frameworks into learning management systems - A technology enhanced learning model for quality education - A hybrid teaching and learning model - Integration of subject related ICT in schools is failing; Could revival of system dynamics and simulations be an example towards improvement? - Student development in higher education: a constructivist approach - Balancing teacher quality and quantity An automatic indicator of the reusability of learning objects based on metadata that satisfies completeness criteria - Recognizing the “Transformational” in preservice digital literature assignments - Getting ready for the “School of the Future”: key questions and tentative answers - Modeling project management competences: an ontology-based solution for competency-based learning - Measuring the quality of the u-learning dervice using the zone of tolerance SERVQUAL - The social network classroom - A process-oriented model for technology-enhanced learning - Extending LMS to support IRT-based assessment test calibration - Family involvement as a priority element for an educational action based on dialogic learning - A threats blocking plug-in for open source learning management systems - Design of an interactive game for teaching war ethics - BriteStep: automation in IT assessment - From empiricism to total quality management in Greek Education - Evolutionary approach of virtual communities of practice: a reflection within a network of Spanish rural schools - Union catalogs of learning objects: Why not? - Evaluation study of pedagogical methods and e-larning material via web 2.0 for hearing impaired people - Towards a pragmatic model for group-based, technology-mediated, project-oriented learning – An overview of the B2C model - Video conferencing and knowledge management in in-service teacher distance lifelong training and development - Supporting teachers to automatically build accessible pedagogical resources: the APEINTA project - Developing the school of the future based on quality principles - Digital literacy development of students involved in an ICTeducational project - SOLE: applying semantics and social web to support technology enhanced learning in software engineering - Retracted: design education in the global era Integrated design of basic training, practicum and end-of-course assignment modules in the teacher training degree: perception of university teachers, students, and school teachers - Students’ satisfaction with an undergraduate primary education teaching practicum design on developing technological, pedagogical and mathematical knowledge - Web-based optimization system applied to the teaching of mathematical programming - New insights and new approaches for lifelong learning - GeoGebra: a global platform for teaching and learning math together and using the synergy of mathematicians - Reducing stress within the rehabilitative work setting – A report on the ROSE project - Teaching for multiple intelligences in undergraduate education - New learning – The IPP programme: improvements in learning and self esteem by changing the organization of learning - Recruitment and rotation of the trainers in the lifelong learning context - Erratum: design education in the global era.